Intramedullary K-wires versus Alternate Techniques for Metacarpal Shaft and Neck Fractures: A Systematic Review and Meta-analysis - Thomas, Terence L.; Kachooei, Amir R.; Ilyas, Asif M. (Journal of Hand and Microsurgery, 2022)
Intramedullary K-wire (IMKW) fixation is one of the mainstays for surgically treating metacarpal shaft and neck fractures. However, there remains a lack of literature comparing outcomes of the various available surgical repair techniques in all indicated metacarpals. Therefore, we conducted a systematic review and meta-analysis to investigate the clinical advantages and drawbacks of IMKW compared with alternate fracture repair techniques. A comprehensive systematic literature review was performed to identify studies that compared clinical outcomes of IMKW to alternate metacarpal fixation modalities. Outcomes included Disabilities of the Arm, Shoulder, and Hand (DASH/quickDASH) scores, grip strength, union rate, visual analog scale pain, operative time, and complications. A random-effects model was used to compare IMKW to the pooled effect of other fixation techniques. A total of 10 studies were included in our analysis, comprising 497 metacarpal fractures (220 shafts and 277 necks). IMKW fixation was identified as the control group in all studies. The pooled experimental group included plates, transverse K-wires (TKWs), interfragmentary screws (IFSs), and K-wire cross-pinning (CP). In treating metacarpal shaft fractures, IMKW showed significantly shorter operative time (p = 0.04; mean difference = − 13; 95% confidence interval = −26 to −0.64). No significant differences were observed in treating metacarpal neck fractures for disability, grip strength, healing rate, pain, operative time, or complication rate. This systematic review and meta-analysis found no difference in clinical outcomes among various surgical techniques for treating metacarpal shaft and neck fractures. Further high evidence studies are required that investigate the efficacy and safety of IFS, CP, TKW, and intramedullary screws versus IMKW for treating closed, unstable metacarpal fractures.
Keywords: fixation techniques; fracture; hand fracture; intramedullary; meta-analysis; metacarpal; metacarpal fracture; surgery; surgical; systematic review